Use of Islamic and Local Wisdom Textbook to Train the Religious Character of Prospective Physics Teachers - Lutfiyanti Fitriah (Universitas Lambung Mangkurat, 2020)
The research aims to describe the religious character and cognitive competence of physics prospective teachers when they used textbook containing Quranic verses. The Quranic verses were relevant to heat and temperature concept then also relevant to local wisdom of South Kalimantan. The research used to research and development, with the development model of ADDIE. The subjects of this research were 18 students of the 2019/2020 academic year who learned heat and temperature topic in Fundamental of Physics 1 course. The data were obtained through a self-evaluation inventory sheet, observation sheet, and test. The data were analysed quantitatively and qualitatively. The result of the research showed that the religious characters of physics prospective teachers from A1 to A5 domain have average score 4.69 which are in very good category and their cognitive competence of C2 to C6 domain improve quite effectively with average normalised gain 0.68. The conclusion of this research is the textbook can be used to train physics prospective teachers to do religious behaviour.